Further observations on LKB1/STK11 status and cancer risk in Peutz-Jeghers syndrome. - Lim, W; Hearle, N; Shah, B; Murday, V; Hodgson, S; Lucassen, A; Eccles, D; Talbot, I; Neale, K; Lim, A; O'Donohue, J; Donaldson, A; et al. (2003)
Germline mutations in the LKB1/STK11 tumour suppressor gene cause Peutz-Jeghers syndrome (PJS), a rare dominant disorder. In addition to typical hamartomatous gastrointestinal polyps and pigmented perioral lesions, PJS is associated with an increased risk of tumours at multiple sites. Follow-up information on carriers is limited and genetic heterogeneity makes counselling and management in PJS difficult. Here we report the analysis of the LKB1/STK11 locus in a series of 33 PJS families, and estimation of cancer risks in carriers and noncarriers. Germline mutations of LKB1/STK11 were identified in 52% of cases. This observation reinforces the hypothesis of a second PJS locus. In carriers of LKB1/STK11 mutations, the risk of cancer was markedly elevated. The risk of developing any cancer in carriers by age 65 years was 47% (95% CI: 27-73%) with elevated risks of both gastrointestinal and breast cancer. PJS with germline mutations in LKB1/STK11 are at a very high relative and absolute risk of multiple gastrointestinal and nongastrointestinal cancers. To obtain precise estimates of risk associated with PJS requires further studies of genotype-phenotype especially with respect to LKB1/STK11 negative cases, as this group is likely to be heterogeneous.